Between Freedom And Protection: A Critical Review Of Indonesia’S Cyberspace Law - Al Asyari, Haekal (Prophetic Law Review, 2023)
Following the COVID-19 pandemic, dependency on the internet—notably, the utilization of cyberspace—has increased, amplifying the virtual domain to a prominent role in everyone’s everyday life. As a country with one of the highest number of internet users in Asia, Indonesia faces challenges of unequal access, limits on content, data privacy, data security, and digital literacy. Given that cyberspace infrastructure is shared between governments, corporations, individuals, and telecommunication providers while individual countries govern the networks, the Indonesian government is under its own exclusive authority to legislate and create policies governing Indonesia’s cyberspace. There has been significant progress toward a legal framework of Indonesia’s cyberspace law, such as the enactment of the Personal Data Protection Law. Unfortunately, such progress is far from being effective. It is evident from Indonesia’s fragmented laws, response-driven policies, and the numerous cyber incidents that have occurred only within the past years. This article investigates Indonesia’s legal-philosophical position in governing the cyberspace. By using a normative methodology, this research crystallizes Indonesia’s position between the freedom or the protectionist approach through analyzing the existing cyberspace regulations. The result of this study shows that Indonesia is somewhere in the middle of liberalizing its cyberspace and protecting it for its national interest. This position could bring both advantages and disadvantages to Indonesia’s cyberspace development.Keywords: Cyberspace, Freedom, Indonesia, Protection. Antara Kebebasan dan Perlindungan: Tinjauan Kritis Terhadap Hukum Dunia Maya Indonesia AbstrakSetelah pandemi COVID-19, ketergantungan pada internet—terutama pemanfaatan dunia maya—telah meningkat, memperkuat domain virtual menjadi peran penting dalam kehidupan sehari-hari setiap orang. Sebagai negara dengan salah satu pengguna internet terbanyak di Asia, Indonesia menghadapi tantangan berupa ketimpangan akses, batasan konten, privasi data, keamanan data, dan literasi digital. Mengingat bahwa infrastruktur dunia maya dibagi antara pemerintah, perusahaan, individu, dan penyedia telekomunikasi sementara masing-masing negara mengatur jaringan, pemerintah Indonesia berada di bawah otoritas eksklusifnya sendiri untuk membuat undang-undang dan membuat kebijakan yang mengatur dunia maya Indonesia. Ada kemajuan signifikan menuju kerangka hukum hukum dunia maya Indonesia, seperti pemberlakuan Undang-Undang Perlindungan Data Pribadi. Sayangnya, kemajuan tersebut jauh dari efektif. Hal ini terlihat dari undang-undang Indonesia yang terfragmentasi, kebijakan yang digerakkan oleh tanggapan, dan banyaknya insiden dunia maya yang terjadi hanya dalam beberapa tahun terakhir. Artikel ini mengkaji posisi filosofis hukum Indonesia dalam mengatur dunia maya. Dengan menggunakan metodologi normatif, penelitian ini mengkristalkan posisi Indonesia di antara pendekatan kebebasan atau proteksionis melalui analisis regulasi dunia maya yang ada. Hasil studi ini menunjukkan bahwa Indonesia berada di tengah-tengah liberalisasi dunia maya dan melindunginya untuk kepentingan nasionalnya. Posisi ini dapat membawa keuntungan dan kerugian bagi perkembangan dunia maya Indonesia.Kata kunci: Cyberspace, Kebebasan, Indonesia, Perlindungan.